Isolation and diagnosis of Staphylococcus aureus from wounds and detection of some virulence factors - Ahmed, Zahraa Ayid (PT. Antis International Publisher, 2024)
The current study aimed to isolate and diagnose S. aureus, test its antibiotic susceptibility, and detect some virulence factors. 150 Clinical samples were collected from Kirkuk Hospital in Kirkuk city for the period from December 2023 to March 2024 from patients who were admitted and hospitalized after consulting the specialist doctor and referring him to the laboratory. Colonies of S. aureus were diagnosed based on the culturing characteristics of the colonies growing on mannitol salt agar medium and blood agar media and incubated at 37 0C for 24 hrs. The results showed that 47 (31.3%) of the samples showed bacterial growth. On the other hand, the results showed that S. aureus was highly resistant to Benzylpenicillin (81.8%), while it was very sensitive to both Nitrofurantion and Gentamicin (90.9%). A DNase test was conducted for clinical isolates of S. aureus, which were isolated from burns and wounds, and the results were 100% in terms of the susceptibility of S. aureus isolates to DNase results. The ability of 47 isolates of S. aureus to produce hemolysin was tested by culturing the bacteria on blood agar medium. The ratios of S. aureus isolates to haemolysin production varied, as evidenced by the data, with 39 (82.98%) isolates exhibiting complete hemolysis. It is concluded from the current study that S. aureus that was isolated from wounds was highly resistant to antibiotics and had dangerous harmful factors that increased the bacterial level in infections.